Heparin improves the mortality of patients with non-pulmonary sepsis-associated ARDS: A MIMIC-IV database analysis based on propensity score matching - Jinfeng Lin; Zhilong Cao; Chunfeng Gu; Lijun Tian; Yadong Wang; Xudong Han (PLoS ONE, 2025)
Background Non-pulmonary sepsis often induces Acute Respiratory Distress Syndrome (ARDS). Dysregulated inflammation and coagulation disorders play important roles in the development of non-pulmonary sepsis-associated ARDS (NPS-ARDS). Heparin, with its potential anticoagulant and anti-inflammatory properties, may be used in the treatment of NPS-ARDS. Methods This is a retrospective observational study that uses Structured Query Language (SQL) to extract clinical data of NPS-ARDS patients from the Medical Information Mart for Intensive Care (MIMIC)-IV database. Based on the dosage of heparin, patients were divided into three groups: low-dose heparin treatment group (0-5000u/d), medium-dose heparin treatment group (5000u-10000u/d), and high-dose heparin treatment group (greater than 10000u/d). Propensity score matching (1:1) was used to match similar patients from the NPS-ARDS patients who did not use heparin to each heparin treatment group. The study compares the effects of heparin at different dosages on short-term mortality (7-day, 28-day, and 60-day mortality) and one-year cumulative survival rate in NPS-ARDS patients. Results PSM reduced the impact of confounding factors on the results to some extent. Low and medium doses of heparin did not improve patient mortality. However, high-dose heparin improved the short-term mortality of NPS-ARDS patients (7-day mortality: 4.1% vs. 14.3%, P < 0.001; 28-day mortality: 9.4% vs. 22.6%, P < 0.001; 60-day mortality: 13.2% vs. 24.8%, P = 0.001) and one-year cumulative survival rate (Log Rank = 8.349, P = 0.004), but it also prolonged ICU stay (6.7 ± 6.2 days vs. 5.7 ± 4.8 days, P = 0.041) and invasive mechanical ventilation (11.7 ± 6.9 hours/day vs. 5.7 ± 4.8 hours/day, P < 0.001). Conclusion In patients with NPS-ARDS, high-dose heparin was associated with significantly improved short- and long-term survival, albeit at the cost of prolonged ICU stay and mechanical ventilation.